Markers in Select Electronic Essays of English Language Students - Marvic M. Casio; Joan O. Sabalberino; Rodel C. Tinonas; Analyn C. Españo (Randwick International of Education and Linguistics Science Journal, 2022)
This study ascertained specific discourse markers used under the categories of contrastive, elaborative and inferential in the selected electronic essays of freshmen Bachelor of Arts in BA English Language students of a government run university in Tacloban City, Leyte, Philippines. It pinpointed the discourse markers that are used incorrectly by the freshmen students in their writings. Using a qualitative research design, the data were sourced from the sixty-two students’ electronic essays, enrolled in the History of the English Language course during the first semester of academic year 2021-2022. The essays were described, analyzed and interpreted using the framework on discourse markers developed by Fraser in 2009. Results showed that the students used restricted set of contrastive (“but” and “however”), elaborative (“and” and “furthermore”), and inferential (“because (of/this)” and “so (that)”) discourse markers (DMs). Furthermore, multiple incorrectly used DMs were also found as caused by misused, unnecessary, non-functional, and ungrammatical DMs. As use of discourse markers seemed restricted among the language students, the researchers found a gap of familiarization with other discourse markers and their functions among them, hence, limiting them to use common discourse markers (e.g. but, and, so that etc.). Moreover, students are also still incognizant with the basic functions and categorization of discourse markers which somehow affect the quality of their electronic essay outputs.